2015
DOI: 10.1177/0022167815571597
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Emotional Experience in Spirituality

Abstract: This study seeks to compare flow and emotional experience in interactive and coactive collective rituals. For such purpose, a correlational study was performed collecting self-report measures of flow, positive emotions, and social identity in three different social collective gatherings: the Sunday celebration of a Catholic mass ( N = 57), a Zen Buddhist meditation practice ( N = 50), and secular Sunday group activities ( N = 37). Results show the presence of flow in all three contexts, being higher in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, exposure to secular contexts such as natural grandeur also produces feelings of awe and enhances prosociality independent of religious belief (Piff et al, 2015;Prade & Saroglou, 2016). Likewise, in one study, the presence of positive emotions and flow were equivalent in those who were engaged in nonspiritual social activities as well as those attending Catholic mass (Rufi et al, 2016). In regards to the elicitation of awe, one study found that reported physical health was improved when Christians were immersed in a cathedral (versus a mosque or museum).…”
Section: Secular Needs Experiences and Practicesmentioning
confidence: 92%
“…For example, exposure to secular contexts such as natural grandeur also produces feelings of awe and enhances prosociality independent of religious belief (Piff et al, 2015;Prade & Saroglou, 2016). Likewise, in one study, the presence of positive emotions and flow were equivalent in those who were engaged in nonspiritual social activities as well as those attending Catholic mass (Rufi et al, 2016). In regards to the elicitation of awe, one study found that reported physical health was improved when Christians were immersed in a cathedral (versus a mosque or museum).…”
Section: Secular Needs Experiences and Practicesmentioning
confidence: 92%
“…Furthermore, a recent study showed that participation in an eating-based collective gathering attended by different ethnic families resulted in improvements in subjective well-being (SWB) including an improved sense of gratitude, hope, optimism, inspiration, love or closeness to other people in general, and social and spiritual connection towards group members (Zumeta 2017). Another study showed that participation in a Zen Buddhist retreat or Catholic mass elicited an experience of shared flow, and activated emotions of calm and serenity when compared with a secular Sunday group activity (Rufi et al 2015). In line with these findings, de Rivera and Carson (2015) argue that reflecting on humanitarian principles in a group gathering could promote a sense of both group and global identity, as well as compassionate intentions towards humanity.…”
mentioning
confidence: 86%
“…Social Identity Theory (Tajfel & Turner, 1986 ) posits that we behave differently in groups to when we are alone. Empirical research on Flow, and emotional experiences in spirituality affirms this to a degree, in a comparison of experiences between people attending a Catholic mass (group), individuals engaging in Zen meditation, and a control group (Rufi et al, 2016 ). Those attending the mass returned higher scores and statistical significance in five out of the nine dimensions on the Flow State Scale—these being ability level (challenge), clear goal, control, action-awareness merging, and concentration (Jackson & Marsh, 1996 ).…”
Section: Suggested Psychological Framework Of Spiritual Experiencesmentioning
confidence: 97%